A MATLAB graphical user interface for battery design and simulation; from cell test data to real-world automotive simulation - Fotouhi, Abbas; Shateri, Neda; Auger, Daniel J.; Longo, Stefano; Propp, Karsten; Purkayastha, Rajlakshmi; Wild, Mark (IEEE, 2016)
This paper describes a graphical user interface (GUI) tool designed to support cell design and development of manufacturing processes for an automotive battery application. The GUI is built using the MATLAB environment and is able to load and analyze raw test data as its input. After data processing, a cell model is fitted to the experimental data using system identification techniques. The cell model's parameters (such as open-circuit-voltage and ohmic resistance) are displayed to the user as functions of state of charge, providing a visual understanding of the cell's characteristics. The GUI is also able to simulate the performance of a full battery pack consisting of a specified number of single cells using standard driving cycles and a generic electric vehicle model. After a simulation, the battery designer is able to see how well the vehicle would be able to follow the driving cycle using the tested cells. Although the GUI is developed for an automotive application, it could be extended to other applications as well. The GUI has been designed to be easily used by non-simulation experts (i.e. battery designers or electrochemists) and it is fully automated, only requiring the user to supply the location of raw test data.
Keywords: Battery; Modelling; Identification; Electric vehicle; EV; Simulation; MATLAB graphical user interface; GUI